Pengaruh Model Pembelajaran Blended Learning Menggunakan Quipper School terhadap Hasil Belajar Matematika Peserta Didik Kelas XI MA Nurul Jadid - Arini Hidayati; Alfi Alufiana Sari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
One of the causes of low student learning outcomes is the use of learning models that are monotonous and tend to be boring, so innovation in learning is needed. The integration of technology into the education and learning process reflects an innovative effort. One model that can make it easier for students to understand and can support technological developments is the blended learning model. Quipper School is an online learning platform that can be used in the blended learning model. This research aims to determine whether or not there is an influence of the blended learning model using Quipper School on the mathematics learning outcomes of class XI MA Nurul Jadid students. This research is quantitative research with a quasi experimental type. The subjects in this research were class XI MIPA 2, totaling 23 people as the experimental class and class XI MIPA 4, totaling 23 people as the control class. Based on the results of the Mann-Whitney U Test, it was found that Asymp. Sig. (2-tailed) of 0.000 is smaller than 0.05, meaning that is rejected and is accepted. Thus, it can be concluded that there is a significant influence from the blended learning model using Quipper School on the mathematics learning outcomes of class XI MA Nurul Jadid students.